SIJJO – LUXURIOUS NATURE QUENIGA CHORLOVCHI GENRE (American Journal of Research in Humanities and Social Sciences, 2023)
This article provides information about the Sijo genre, which appeared in Korea during the Joseon (Li) period of literature (1392-1910). This genre is considered to be a lyrical genre with a certain excitement and experience image, and it incorporates Korean folklore traditions and three religious-philosophical teachings of the people of the Far East (Confucianism, Buddhism and Taoism).